Effects of aromatic compounds on movement activity of Pyrrhocoris apterus in the conditions of a laboratory experiment - V. V. Nehrii; V. V. Brygadyrenko (Regulatory Mechanisms in Biosystems, 2022)
In the conditions of an urban environment, insects, including Pyrrhocoris apterus (Linnaeus, 1758) (Hemiptera, Pyrrhocoridae), are subject to dozens of volatiles: solvents, food flavorings, cosmetic products. For firebugs, some attract them, some scare them off, and to some they are indifferent. In this article, in the conditions of laboratory experiment, we evaluated the influence of chemical substances on rates of movement of firebugs. Under the influence of the substances we studied, there occurred no significant increase or decrease in the activity of firebugs. The most significant effect on rates of movement of firebugs was exerted by solvent, white spirit and solvent 646 p – firebugs travelled 12 cm distance for 24.2%, 49.6% and 58.7% of the time the control group did. Movement activity of firebugs was insignificantly decreased by aromatic extracts Royаl milk extract, Butcher’s broom extract and chrysalis oil: firebugs travelled 12 cm distance for 132.7%, 135.2% and 146.8% of time the control group. Aromatic substances likely interact with receptors on antennae of firebugs, and therefore the insects need additional time for orienting reactions, deciding whether those substances signal presence of potential food objects in the accessibility zone.